If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2 = 3x + -18 Combine like terms: 7 + -2 = 5 5 = 3x + -18 Reorder the terms: 5 = -18 + 3x Solving 5 = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -3x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -3x = -18 + 0 5 + -3x = -18 Add '-5' to each side of the equation. 5 + -5 + -3x = -18 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -18 + -5 -3x = -18 + -5 Combine like terms: -18 + -5 = -23 -3x = -23 Divide each side by '-3'. x = 7.666666667 Simplifying x = 7.666666667
| X*(x+7)=411 | | f(0)=(2x-5)2 | | 8n+1=4n-14 | | X*x+7=411 | | 4(3z-1)-4(z+8)=5(z+1) | | 3-2(x+2)=3 | | 20*6-18*6-6=12 | | 1/2x^2-36=0 | | 5(2x-11)=3x+9 | | 3/5.22 | | 4(x+1)-2(-x-1)=0 | | 12+10=10+12 | | 6x-30+1=0 | | 3-7(-x+5)=2x+5 | | 40(x)+60(y)=1700 | | 8(x-1)-2(3x+4)=0 | | 4x^2+9y^2-8x-54y-59=0 | | ln(3x+2)-ln(2)=1 | | ln(x^3+x^2-2)=ln(x-1)(x^2-1) | | X+2x-1=11 | | 10x-24=4x | | x^2=8-9x | | 3.25n+2=3n+6 | | -3x+6=-6x | | 5y+11=(3y+7) | | 4w(7w+3)=0 | | -2x+9x+5=0 | | 4x^4+36x^3= | | (t+2)(6t+1)=0 | | 7.5x-2.5=20.0 | | 11x+37=90 | | 36x4/9= |